Social cognitive drivers of farmer learning behaviour in the student-to-farmer university outreach in Uganda - Kalule, S.W.; Sseguya, H.; Ongeng, D.; Karubanga, G. (Informa UK Limited, 2019)
Globally, universities are repositioning themselves for community outreach although with difficulty in responding to the unpredictable social features of host communities. Accordingly, this study aims to assess the role of social cognitive factors in farmer learning behaviour during university outreach. Structural equation modelling was conducted on the data obtained from a sample of 283 host participants of the student outreach programme of Gulu University, Uganda. The results indicate that social outcome expectations (β = 0.227, t = 1.978, P < 0.05), social influence (β = .372, t = 4.448, P < 0.01) and farmers’ formation of intentions (β = .214, t = 3.254, P < 0.01) significantly predict farmer learning behaviour. It is also established that social influence combine with formation of intentions to mediate social outcome expectations in predicting farmer learning behaviour. We highlight that tapping into the social setting of host farmers is critical for the success of university outreach in the sense that it generates the social reinforcements for effective farmer participation and learning. We recommend that the managers of university outreach programmes should devote efforts to prepare students to be sensitive to the concerns and needs of the community as a whole rather than just the host farmers.